Amnesty And Tax - Mardiana Ruslan; Fitriani Fitriani; Lenny M. Possumah; Ririn Apriana M. Nur; Nurcahya Hartaty Posumah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this study is to determine the extent to which tax amnesty provides relief from administrative fines linked to motor vehicle taxes. The descriptive research technique chooses to use analysis with a qualitative approach before making conclusions. Tables and diagrams are used to depict the realization of motor vehicle tax income before and after the tax amnesty. The results of the survey show that because of the Amnesty tax relief program, more people in the city of Bandung are aware of paying motor vehicle taxes. This tax amnesty program also raises the original regional revenue in the motor vehicle tax sector until the predetermined objective is reached.